STATE REGULATION OF PENSION PROVISION AND SOCIAL DEVELOPMENT (INNOVATIVE ECONOMY, 2020)
Drabyk O.M. STATE REGULATION OF PENSION PROVISION AND SOCIAL DEVELOPMENTPurpose. The aim of the article is the conducting a study on state regulation of retirement provision and identifying key levers of social impact.Methodology of research. The dialectical method of scientific knowledge, systemic and logical approaches is used to accomplish research tasks and achieve the set goal. The following general scientific methods are used in the course of the research: economic and statistical – to characterize the state of state regulation of the social sphere; table and graphic – for visual display of research results in tables, diagrams; abstract and logical – in the formation of conclusions and proposals.Findings. The main levers of state regulation of pension provision in the context of social development in Ukraine are determined. It was found that the country's pension system is negatively affected by the state of employment, in particular unemployment, migration processes. It has been established that the current system of solidarity will not be able to exist for so long and provide citizens with statutory pension provision taking into account the economic situation in Ukraine.It is substantiated that the main direction for solving the problem is to create a favorable investment climate that would provide conditions for launching a multilevel pension system and contributing to proper social protection.Originality. The causes of the pension crisis crisis, which are connected with the worsening of the legalization of earnings are determined. It is substantiated that it is necessary to solve the problem of employment by creating additional jobs and restraining migration processes for solving the existing problems of pension provision.The following statements have gained further development: analytical tools for assessing the state of retirement provision; mechanisms for ensuring the pension system on the basis of the comprehensive consideration of the features of self-reproduction, self-development and self-regulation of the pension system. Improving their effectiveness involves the development of self-regulation processes, providing an organic combination of centralized management and independence of subsystems. It is established that the interaction of public and private partnership will facilitate the provision of innovative development of the pension system.Practical value. The results of the study can be used in the organs of the Pension Fund and the social sphere, and some theoretical and practical provisions, in particular, the mechanisms of providing the pension system on the basis of the comprehensive consideration of the features of self-reproduction, self-development and self-regulation of the pension system – in educational processes and in the research work of teachers, postgraduates, students.Key words: state regulation; social protection; social sphere; pensions; pension systems; pension provision; unemployment; migration
Keywords: Key words; state regulation; social protection; social sphere; pensions; pension systems; pension provision; unemployment; migration